High-harmonic and single attosecond pulse generation using plasmonic field enhancement in ordered arrays of gold nanoparticles with chirped laser pulses - Yang, Ying-Ying; Scrinzi, Armin; Husakou, Anton; Li, Qian-Guang; Stebbings, Sarah L.; Süßmann, Frederik; Yu, Hai-Juan; Kim, Seungchul; Rühl, Eckart; Herrmann, Joachim; Lin, Xue-Chun; Kling, Matthias F. (My University, 2013)
Coherent XUV sources, which may operate at MHz repetition rate, could find applications in high-precision spectroscopy and for spatio-time-resolved measurements of collective electron dynamics on nanostructured surfaces. We theoretically investigate utilizing the enhanced plasmonic fields in an ordered array of gold nanoparticles for the generation of high-harmonic, extreme-ultraviolet (XUV) radiation. By optimization of the chirp of ultrashort laser pulses incident on the array, our simulations indicate a potential route towards the temporal shaping of the plasmonic near-field and, in turn, the generation of single attosecond pulses. The inherent effects of inhomogeneity of the local fields on the high-harmonic generation are analyzed and discussed. While taking the inhomogeneity into account does not affect the optimal chirp for the generation of a single attosecond pulse, the cut-off energy of the high-harmonic spectrum is enhanced by about a factor of two.
Keywords: Single attosecond pulse generation; Extreme-ultraviolet (XUV) radiation